Unraveling the Lipidome and Antioxidant Activity of Native Bifurcaria bifurcata and Invasive Sargassum muticum Seaweeds: A Lipid Perspective on How Systemic Intrusion May Present an Opportunity - Fábio Santos; João P. Monteiro; Daniela Duarte; Tânia Melo; Diana Lopes; Elisabete da Costa; Maria Rosário Domingues (MDPI AG, 2020)
Brown seaweeds are known to present components with appealing bioactive properties eliciting great interest for industrial applications. However, their lipid content is generally disregarded beyond their fatty acid (FA) composition. This study thoroughly characterized the lipid profile of two brown seaweeds collected from Portuguese coast, the native Bifurcaria bifurcata and the invasive Sargassum muticum species, and bioprospecting for antioxidant activity. An integrated state-of-the-art approach including gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (HILIC-ESI-MS/MS), allowed a comprehensive picture of FA and polar lipid content. Polar lipid profile of B. bifurcata and S. muticum included 143 and 217 lipid species respectively, distributed between glycolipids, phospholipids, and betaine lipids. Some of the lipid species found have been assigned biological activity and contain of n-3 and n-6 FA. Sargassum muticum presented the highest n-3 FA content. Low concentrations of extracts of both seaweeds displayed antioxidant activity, with S. muticum presenting more promising results. These findings contribute to the nutritional and industrial exploitation of both seaweeds, highlighting their relevance as viable sources of bioactive and added-value compounds. Sargassum muticum presented interesting lipid composition and bioactivity, which may represent an accessible opportunity for the exploitation of this invasive seaweed, especially taking advantage of Sargassum blooms.